Impaired DNA-binding affinity of novel PAX6 mutations - Lee, Seowhang (Sci Rep, 2020)
Mutations in human PAX6 gene are associated with various congenital eye malformations including aniridia, foveal hypoplasia, and congenital nystagmus. These various phenotypes may depend on the mutation spectrums that can affect DNA-binding affinity, although this hypothesis is debatable. We screened PAX6 mutations in two unrelated patients with congenital nystagmus, and measured DNA-binding affinity through isothermal titration calorimetry (ITC). To elucidate phenotypic differences according to DNA-binding affinity, we also compared DNA-binding affinity among the previously reported PAX6 missense mutations within the linker region between two subdomains of the paired domain (PD). We identified two novel mutations of PAX6 gene: c.214 G > T (p.Gly72Cys) and c.249_250delinsCGC (p.Val84Alafs*8). Both were located within the linker region between the two subdomains of the PD. ITC measurement revealed that the mutation p.Val84Alafs*8 had no DNA-binding affinity, while the p.Gly72Cys mutation showed a decreased binding affinity (Kd = 0.58 μM) by approximately 1.4 times compared to the wild type-PAX6 (Kd = 0.41 μM). We also found that there was no close relationship between DNA-binding affinity and phenotypic differences. Our results suggest that the DNA-binding affinity alone might be insufficient to determine PAX6-related phenotypes, and that other modifier genes or environmental factors might affect phenotypes of the PAX6 gene.